Sulla voce ne La nota segreta di Marta Morazzoni - Kornacka, Barbara (Studia Romanica Posnaniensia, 2018)
The aim of the article is to analyze the meanings of the voice in the novel mentioned in the title in relation to Adriana Cavarero’s thought. Following the presentation of the work, the article examines two different manifestations of the voice in the text: the singing voice and the discursive voice. The former confirms the patriarchal association of women with the body but sometimes it also appears as a space of freedom from oppression. The latter, which is denied to the protagonist, symbolizes women’s exclusion from logos.